Analisis Faktor-Faktor yang Mempengaruhi Keterlambatan Penyelesaian Audit pada Perusahaan Manufaktur yang Listing pada Bursa Efek Indonesia (BEI) Tahun 2018-2021 - Moh Khairuddin Kurniansyah; Anik Malikah; Junaidi Junaidi (Universitas Islam Malang, 2023)
The research was conducted to ensure factors that affect delay in to completion of audits in manufacturing companies listed on the Indonesia Stock Exchange. This research is categorized as causal research, namely research based on the characteristics of the problem that has a cause-and-effect relationship between two or more variables. In this study, the authors took samples from Manufacturing Companies that have been listed on the IDX in 2018, 2019, 2020, and 2021. The sampling technique was carried out by purposive sampling, so that a sample of 43 manufacturing companies was obtained. The method of data analysis used is multiple linear regression analysis. Based on the tests that have been carried out, it can be concluded that the results of partial simultaneous tests indicate that Company Size, Public Accounting Firm Size and Profitability have a significant effect on Audit delay. While the partial test shows that the Audit Opinion has no effect on the Audit delay.Keywords: Audit delay, firm size, public accounting firm size, audit opinion, profitability, manufacturing company.